2020
DOI: 10.1021/acs.energyfuels.0c01862
|View full text |Cite
|
Sign up to set email alerts
|

Macroscopic Kinetic Investigations on Mixed Natural Gas Hydrate Formation for Gas Storage Application

Abstract: Solidified natural gas (SNG) technology via clathrate hydrates is a promising technology for the long-term and largescale storage of natural gas, owing to multifaceted benefits offered, including environmentally benign, compact, and safest mode of gas storage in comparison to conventional methods. In this study, we investigate the macroscopic kinetics of natural gas hydrate formation using a C1 (93%)−C2 (5%)−C3 (2%) gas mixture. The main objective is to examine the effect of the presence of low concentrations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
30
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(37 citation statements)
references
References 40 publications
2
30
0
Order By: Relevance
“…The remaining two cylinders provide bias values for the reservoir and the crystallizer. Omega Class A platinum resistance temperature detectors are used to 2), reservoir bias (3), reservoir (4), crystallizer (5), magnetic stirrer (6), electric stirrer (7), sample injection port (8), and methane cylinder (9). DP and CV represent differential pressure and the control valve, respectively.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The remaining two cylinders provide bias values for the reservoir and the crystallizer. Omega Class A platinum resistance temperature detectors are used to 2), reservoir bias (3), reservoir (4), crystallizer (5), magnetic stirrer (6), electric stirrer (7), sample injection port (8), and methane cylinder (9). DP and CV represent differential pressure and the control valve, respectively.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…Although much research has been focused on the inhibition of hydrate formation, they are now being studied for use in novel industrial applications. Their selective formation processes and high gas storage potentials have made them optimal candidates for natural gas storage and transport, separation processes including desalination, and atmospheric carbon removal via carbon dioxide sequestration. , …”
Section: Introductionmentioning
confidence: 99%
“…8 Natural hydrates are ascertained to be a future energy source if used with feasible technology and will have economic value. 9 The synthetic hydrates provide multifaceted applications such as storage media for greenhouse gases, [10][11][12][13][14][15][16] carbon dioxide capture from fuel gas, 17 methane recovery from coal mine gas, 18,19 desalination, [20][21][22] cold storage, [23][24][25][26][27] and gas transportation. 12,28 Because of their structural properties and selectivity, this process slowly escalates to address various food technology issues.…”
Section: Gas Hydratesmentioning
confidence: 99%
“…Different guest molecules have different influences on the stability of hydrate structures, as well as the fusion behavior of multi-cages. Studies have been promoted to explore the influence of mixed guest molecules in hydrates [ 8 , 16 , 21 , 22 , 23 , 24 ]. Su et al reported that structure II (sII) type clathrate crystal is thermodynamically stable when the hydrates are partially or fully occupied with three different guest molecules (CH 4 , C 2 H 6 , and C 3 H 8 ) [ 7 ].…”
Section: Introductionmentioning
confidence: 99%